Beyond the shrinking world: dementia, localisation and neighbourhood. Issue 12 (22nd December 2022) - Ward, Richard; Rummery, Kirstein; Odzakovic, Elzana; Manji, Kainde; Kullberg, Agneta; Keady, John; Clark, Andrew; Campbell, Sarah
Abstract: 'Dementia-friendly communities' herald a shift toward the neighbourhood as a locus for the care and support of people with dementia, sparking growing interest in the geographies of dementia care and raising questions over the shifting spatial and social experience of the condition. Existing research claims that many people with dementia experience a 'shrinking world' whereby the boundaries to their social and physical worlds gradually constrict over time, leading to a loss of control and independence. This paper reports a five-year, international study that investigated the neighbourhood experience of people with dementia and those who care for and support them. We interrogate the notion of a shrinking world and in so doing highlight an absence of attention paid to the agency and actions of people with dementia themselves. The paper draws together a socio-relational and embodied-material approach to question the adequacy of the shrinking world concept as an explanatory framework and to challenge reliance within policy and practice upon notions of place as fixed or stable. We argue instead for the importance of foregrounding 'lived place' and attending to social practices and the networks in which such practices evolve. Our findings have implications for policy and practice, emphasising the need to bolster the agency of people living with dementia as a route to fostering accessible and inclusive neighbourhoods.